Assistance to the Transition Economies : Were There Alternatives? - Svejnar, Jan (World Bank, Washington, DC, 2014)
Twelve years after the fall of the Berlin Wall, domestic and international analysts of the transition economies by and large agree that the transition from central planning to a market economy has been exceedingly difficult. There has also been a major debate about the extent to which the transition to date has succeeded or failed. This paper provides an assessment of the policies that were followed and discuss the extent to which there were known alternatives that can have resulted in superior outcomes in terms of: (a) gross domestic product (GDP) growth and other principal performance indicators, (b) building honest and competent institutions, and (c) creating a more transparent and less corrupt system of corporate and national governance. Section two provides a brief overview of performance since 1989. Section three presents the recommendations that were made and policies that were followed. The paper concludes in section four by assessing the extent to which alternative paths can have been followed and what the likely outcomes will have been.